Enhancing Arts Education with Chrome Music Lab: An Experiential Learning Approach in Practice - Krispra Tomi Soeharto; Suci Fajrina; Rosta Minawati; Iswandi (Program Studi Pendidikan Musik FBS UNP, 2026)
Objective: This study aims to facilitate knowledge transfer to students through resources such as printed texts, audio recordings, or multimedia presentations, all designed to help students grasp concepts more concretely. Method: The study employs a literature review methodology, analyzing various materials related to the integration of Chrome Music Lab in experience-based arts education. Results and Discussion: Findings indicate that integrating Chrome Music Lab empowers educators to create a more dynamic, engaging, and impactful learning environment. Chrome Music Lab, developed by Google, is an online educational platform offering a variety of interactive components to explore musical instruments, sound, and digital music, specifically designed for young audiences. Experiential Learning Strategies emphasize direct interaction between teachers and students to support understanding, skill development, and reflection through hands-on practice. Conclusion: Through this medium, students acquire knowledge by actively participating in music creation and interpretation, fostering high motivation, creativity, and strong engagement in arts education.